Pharmacokinetic Characteristics of Tofacitinib in Adult Patients With Moderate to Severe Chronic Plaque Psoriasis. Issue 6 (1st June 2018) - Ma, Guangli; Xie, Rujia; Strober, Bruce; Langley, Richard; Ito, Kaori; Krishnaswami, Sriram; Wolk, Robert; Valdez, Hernan; Rottinghaus, Scott; Tallman, Anna; Gupta, Pankaj
Abstract: Tofacitinib is an oral Janus kinase (JAK) inhibitor. This study characterized the pharmacokinetics of tofacitinib in patients with psoriasis and evaluated the impact of patient factors on disposition. Pooled phase 2/3 data (2981 patients: 9735 concentrations, dose range: 2‐15 mg twice daily) up to 56 weeks were used for modeling. A one‐compartment model parameterized in terms of apparent oral clearance (CL/F), apparent volume of distribution, zero‐order absorption (duration, D), with interindividual variability and inter‐occasion variability terms, described tofacitinib pharmacokinetics. A full covariate model incorporated effects for age, sex, race, ethnicity, and baseline variables (body weight, Psoriasis Area Severity Index [PASI], C‐reactive protein [CRP], creatinine clearance [CrCl]). The parameter estimates (95%CI) for CL/F, Vd/F, and D in a typical individual (white, male, 86 kg, 46 years, CrCl 121 mL/min, PASI 19.8, and CRP 0.267 mg/dL) were 26.7 (25.9, 27.5) L/h, 125 (120.8, 128.3) liters, and 0.69 (0.646, 0.735) hours, respectively. Only CrCl led to clinically relevant changes in exposure. The analysis suggested no dosing modifications for age, body weight, sex, race, ethnicity, baseline PASI, or CRP based on the magnitude of exposure change. Dosing adjustments for renal impairment were derived from a separate phase 1 study.